FACTORS AFFECTING DECISIONS OF FARMERS USING CREDIT UNION (CU) KELING KUMANG AS FINANCING INSTITUTIONS OF FARMING IN DESA PIAWAS KECAMATAN BELIMBING HULU KABUPATEN MELAWI - Agustinus, Agustinus; Sudrajat, Jajat; Suyatno, Adi (Jurnal Sains Pertanian Equator, 2019)
Keling Kumang Credit Union Cooperative is a savings and loan financial institution for the community in Piawas Village. This study aims to analyze the decision-making factors of farmers using (CU) as a source of farming finance. Data were analyzed using logit regression method. The results of this study indicate that total income, family expenses and the number of dependents do not have a significant partial effect on decisions. Factors that influence farmers' decisions are Education Level. Keywords: Financing, Farming, Member Decision, and Logit Regression